Il teatro "en travesti" del KTTMCC alias Pumitrozzole - Grimaldi, Claudio (Mimesis Journal, 2021)
Among the numerous gay performers appearing in off and off-off Italian theatres towards the end of the Seventies one group stood out: the flamboyant and diverse KTTMCC (Kollettivo Teatrale Trousse Merletti Cappuccini e Cappelliere, which could loosely be translated by Theatre Kollective Cosmetic bags, Laces, Cappuccinos and Hat boxes). In its brief but intense life the group performed in theatres, crowded public spaces, and tiny dark venues, always proposing outrageously camp political and social statements. The art of Dada and a taste for camp-ish kitsch seemed to have heavily influenced their “actions” and shows. “The sublime from above and the sublime from below coincide”. They appeared onstage in drag, not the polished and hyper-feminine type of drag popular with the mainstream gay bars clientele, but an ironic, trashy and playful one that came from their texts and from a blend of authentic high-end designer outfits, department stores little dresses, fashionable boots, dangerous platform shoes bought in thrift shops, statement costume jewelry and very, very accurately back-combed wigs. In this text, the author proposes a meeting/interview to three of the original members of the collective, Silvio, Guglielmo and Paolo, now living in different Italian cities, to gather useful information on the KTTMCC’s beginnings and on its decade- long “career” which ended with the controversial TV fame of one of its members, Platinette (boku de cû boku de tet).